(2013) Minister Wert's first year of educational policy - Sanjosé, Jesús (Razón y fe, 2018)
The Minister of Education, Culture and Sports, José Ignacio Wert, following the program with which his party, the PP, won the elections in November 2011, has initiated the modification of educational legislation. During the month of August 2012 it has issued two Royal Decrees, aimed at modifying the contents of the subject of Education for Citizenship, and in October it has presented for its approval to the Council of Ministers the preliminary draft of the organic law to improve educational quality . Given that at least three drafts of this preliminary draft for the Improvement of Educational Quality have been circulated at this time, I will limit myself on this occasion to raising some general aspects, leaving for later the specific analysis of the measures that are finally sent to Congress.